"Your Doctor Won’t Tell You This ...": Expert and Lay Perspectives in Health Communication Discourse - Abrahamson, Jennie A.; Rubin, Victoria L. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
We investigate health care provider and lay consumer perspectives in online health communication, information sharing, and use to improve communication that supports healthy everyday life behavior. With Rhetorical Structure Theory analysis, we differentiate discourse structure patterns and communicative goals in provider and consumer answers regarding a chronic condition - diabetes. Nous investiguons les perspectives des professionnels et des usagers du système de soins de santé en matière de communications en ligne, d’échange et d’utilisation d’information médicale pour améliorer les comportements quotidiens sains. À l’aide d’une analyse des réponses basée sur la théorie de la structure rhétorique, nous discriminons les modèles de structure de discours et les objectifs communicationnels des fournisseurs et des usagers concernant une maladie chronique : le diabète.